(3JPgjH GdJgPjHs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3eMeO Hf YHO dGdg Hf YHO GdQMef GdCTYQi s)
(3ChdgG (B:s
(3YHjO Gddg Hf YHO GdcQje Hf jRjO Hf aQhN GdeNRhei GdGeGe CHh RQYI GdQGRi s
(3BNQgG (B:s
(3bGd GdfSGFi (B: (3dG HCS Hg bjd eGJ HYO GdNeSjf BNQ GdSaQ GdKGdK ef JPgjH GdJgPjH jJdhg ai GdQGHY Ef TGA Gddg (B: (3eGdc Hf OjfGQ s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs